Mycoplasmateceae Species Are Not Found in Fallopian Tubes of Women with Tubo-Peritoneal Infertility - Fuhrer-Fuster, J; Cardenas-Sankan, G; Costoya-Arrigoni, A (2012)
Background: The role of mycoplasmas on the development and sequelae of pelvic inflammatory disease remains controversial. The objective of the present study is to correlate directly the presence of Mycoplasmateceae through polimerase chain reaction (PCR) determinations in cervix and Fallopian tubes of infertile patients with tubo-peritoneal factor diagnosed through laparoscopy. Methods: Thirty patients with tubo-peritoneal infertility and 30 normal fertile patients were included in the study; cervical samples and tubal flushings were obtained during laparoscopy. PCR determinations for the detection of genetic material of Mycoplasma genitalium, Mycoplasma hominis, Ureaplasma urealiticum, Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis in cervix and tubal flushings were performed. Results: No Mycoplasmataceae species as "only" microorganisms were found in tubal flushings of tubo-peritoneal infertility patients, whereas three (10%) fertile patients with normal tubes were positive for mycoplasma presence. This difference was not significant (p = 0.237). Among the 30 patients suffering from tubal infertility diagnosed through laparoscopy, Mycoplasmatecae species were not detected in the Fallopian tubes by PCR determinations, while in normal tubes from fertile patients these and other microorganisms could be found without distorting tubal anatomy. Conclusion: Mycoplasmateceae species were not detected in Fallopian tubes of women with tubo-peritoneal infertility. © 2012 Elsevier Editora Ltda.